Honey bees bred for Varroa sensitive hygiene trait demonstrate resistance to chalkbrood disease - Isabell Dyrbye-Wright; Michael Simone-Finstrom; Elizabeth M. Walsh; Marla Spivak (PLoS ONE, 2025)
To improve health and vitality of honey bees (Apis mellifera) beekeepers can propagate stocks that demonstrate resistance to both parasites and pathogens. Most breeding programs focus on resistance to Varroa destructor mites and/or brood pathogens. Colonies bred specifically for the trait Varroa Sensitive Hygiene (VSH), exhibit a high level of resistance to the parasitic mites. Still, they have never been explicitly tested for resistance to brood diseases. The goal of this study was to test if colonies bred for VSH are both mite and disease resistant. Over two years (2023 and 2024) and in two locations (University of Minnesota and the USDA-ARS lab in Baton Rouge, Louisiana), we compared colonies from the Pol-line bred specifically for VSH to colonies from a commercial source. The Commercial colonies in this study were not selected specifically for Varroa resistance but were selected for “general” hygienic behavior using the freeze-killed brood (FKB) assay. We challenged colonies within each line with Ascosphara apis, a fungus that causes chalkbrood, and quantified mites, disease and hygienic behavior. Our study demonstrated that bees from the Pol-line bred for VSH are just as resistant to chalkbrood as bees from a commercial line bred for hygienic behavior. Results confirmed that the Pol-line was more mite resistant than the Commercial, as it had significantly lower mites in two of three trials. Both the Pol-line and Commercial colonies had high levels of hygienic behavior. These results indicate that VSH-selected honey bees respond to both mite-infested and disease-infected brood. Further comparative studies are needed to clarify any differences in genetic mechanisms and olfactory sensitivity mediating the VSH-trait and general hygienic behavior. On a practical level, using honey bees selected for VSH in beekeeping operations could help curb losses, improve honey bee health, and reduce financial burdens caused by Varroa and diseases.